Comparison of Childhood Caries Levels between Children of Pediatric Dentists and Children of General Dentists: A Cross-Sectional Study - Sarit Naishlos; Sigalit Blumer; Sagit Nissan; Joseph Nissan; Johnny Kharouba (MDPI AG, 2023)
Caries development in children is a prevalent childhood disease. Factors affecting chronic teeth lesions include nutrition, parental involvement, and executing proper dental health attitude. Professional dentists are perceived as role models for the oral health and hygiene of their families. The purposes of the research were 1. To compare caries rates in the children of pediatric dentists and children of general dentists. 2. To compare children's nutrition habits between pediatric dentists and general dentists. 3. To compare children's oral health and hygiene between pediatric dentists and general dentists. 4. To compare children's usage of fluoride-containing products between pediatric dentists and general dentists. A cross-sectional study was conducted by distributing self-reporting questionnaires to pediatric dentists and general dentists via the social media "snowball" platform. The following themes were surveyed: nutrition habits and oral hygiene of the children. The sample consisted of 176 participants. Children of pediatric dentists were found to have fewer cases of caries than children of general dentists (p = 0.018). Nutrition habits did not differ between the two groups. In addition, pediatric dentists reported that their children use more fluoridated toothpaste in comparison with general dentists. Professional training of pediatric dentists contributed to shaping the oral hygiene attitude of their children.